African American Academic Librarians: An Evidence Map Case Study Using Rapid Review Methodology. Issue 4 (1st October 2016) - Jefferson, Jasmine L.; Fehrmann, Paul
ABSTRACT: This article explores rapid review and evidence mapping methodology to map library literature on the presence of, status of, or support for African American academic librarians. Rapid reviews include transparent steps and are completed in a short time frame. Evidence mapping is emerging as a way to summarize evidence. A chronological map indicated topics and impacts of papers. Additional analysis also showed four broad themes: diversity, recruitment, retention, and racism. In our view, rapid review and evidence mapping methods should be considered by academic librarians. Further research should look at racism that still seems apparent in academic libraries.